GLOBALIZATION AND METAL REPOUSSÉ CRAFT OF VARANASI: CHALLENGES AND OPPORTUNITIES - Pathak, Sachin; Dave, Dushyant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Varanasi, on the Ganges River in India, is recognized for its old crafts and culture. Metal repoussé is one of several art forms that reference millennia-old aesthetics and methods. Varanasi metal repoussé had problems and possibilities with globalisation. This abstract explores Varanasi's metal repoussé craft's complex relationship with globalisation, its problems, and potential for sustainable expansion. Globalisation has benefited and hurt Varanasi crafts like metal repoussé. Artists may present their work abroad with greater connection and market access, boosting economic and cultural interchange. Globalisation causes loss of authenticity, mass-produced replacements, and artisan exploitation for profit. Metal repoussé artists in Varanasi battle to preserve their skills and creations despite progress. Globalisation might destroy ancient traditions. Customers want quicker, cheaper goods; therefore, craftspeople must decrease their quality and authenticity requirements to compete. Globalisation has commercialized craft, turning it into commodities. Commercialization devalues each piece's work, ability, and cultural relevance, exploiting artists who are already suffering. Despite these constraints, globalisation may reinvigorate Varanasi's metal repoussé craft. One solution is using digital networks and technology to reach more people while retaining creative expression. Handicrafts are respected more because internet markets and social media allow craftspeople to exhibit their work, engage with buyers, and share their story. Collaborations with cultural organisations, historians, and designers may modernize and experiment with methods. Craftspeople may attract more customers and stay up with the market by incorporating new ideas and design features while keeping their trade. Varanasi craftsmen may benefit on the rising demand for environmentally and ethically manufactured goods by presenting their products as cultural heritage and sustainability. Craftspeople may attract socially conscious clients by emphasising local resources, eco-friendly processes, and fair trade. In today's globalized world, the Varanasi metal repoussé craft has many obstacles but also many potentials for development and creativity. Collaboration, technology, and historical preservation help craftspeople participate in the global market.